Field Application of Wuyiencin Against Sclerotinia Stem Rot in Soybean - Yang, Miaoling; Han, Xiaoqing; Xie, Jiabei; Zhang, Shangqing; Lv, Zhaoyang; Li, Boya; Shi, Liming; Zhang, Kecheng; Ge, Beibei (Frontiers in Sustainable Food Systems, 2022)
Sclerotinia stem rot, caused by Sclerotinia sclerotiorum, is a devastating disease of soybean. Biological control is a potential alternative to chemical fungicides for disease management, and provides broad benefits to the environment, farmers and consumers. Herein, we established a field application technique for biocontrol of Sclerotinia stem rot in soybean using wuyiencin, expanding on a previous study showing biocontrol potential. We used wuyiencin to reduce sclerotia in soybean seed, and disease incidence analysis by seed bioassay revealed an optimal wuyiencin seed soaking concentration of 12.5 μg/mL. We found that different application methods had different effects on soybean plant growth. Soybean pot experiments showed that 100 μg/mL wuyiencin was obtained a significant disease protection effect and promote soybean growth through root irrigation, and the optimal concentration for wuyiencin spraying was 100–200 μg/mL. We tested the efficacy of applying wuyiencin under field conditions, and the protection effect of 200 μg/mL wuyiencin sprayed three times was the best (64.0%), but this was slightly inferior to the protection effect of 200 μg/mL dimethachlon (77.6%).